2016
DOI: 10.1094/pdis-03-16-0271-re
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Field Evaluation Reveals Huanglongbing Resistance inCitrusRelatives

Abstract: Citrus huanglongbing (HLB) is a destructive disease with no known cure. To identify sources of HLB resistance in the subfamily Aurantioideae to which citrus belongs, we conducted a six-year field trial under natural disease challenge conditions in an HLB endemic region. The study included 65 Citrus accessions and 33 accessions belonging to 20 other closely related genera. For each accession, eight seedling trees were evaluated. Based on quantitative polymerase chain reaction analysis of the pathogen titers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
168
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(184 citation statements)
references
References 48 publications
4
168
0
1
Order By: Relevance
“…C Las is a heat-tolerant gram-negative bacteria, resides only in the phloem of plant hosts, and is vectored by the sap-sucking Asian citrus psyllid (ACP, Diaphorina citri ) (Wang et al , 2017a). As an obligate and insect-transmitted plant pathogen, C Las attacks all species and hybrids in the genus of Citrus as well as some closely related genera (Ramadugu et al , 2016). Species infected include sweet orange ( Citrus sinensis ), mandarin ( Citrus reticulata ), pummelo ( Citrus maxima ), citron ( Citrus medica ), grapefruit ( Citrus paradisi ), lemon ( Citrus limon ), lime ( Citrus aurantifolia ), kumquat ( Citrus japonica ), and orange jasmine ( Murraya paniculata ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C Las is a heat-tolerant gram-negative bacteria, resides only in the phloem of plant hosts, and is vectored by the sap-sucking Asian citrus psyllid (ACP, Diaphorina citri ) (Wang et al , 2017a). As an obligate and insect-transmitted plant pathogen, C Las attacks all species and hybrids in the genus of Citrus as well as some closely related genera (Ramadugu et al , 2016). Species infected include sweet orange ( Citrus sinensis ), mandarin ( Citrus reticulata ), pummelo ( Citrus maxima ), citron ( Citrus medica ), grapefruit ( Citrus paradisi ), lemon ( Citrus limon ), lime ( Citrus aurantifolia ), kumquat ( Citrus japonica ), and orange jasmine ( Murraya paniculata ).…”
Section: Introductionmentioning
confidence: 99%
“…Breeding and development of HLB resistant or tolerant cultivars is widely regarded to be the most practical strategy to support long-term control of this severe disease in the field. The reports of variability for resistance or tolerance to HLB within citrus and its relatives encourages breeding and selection for resistant or tolerant genotypes (Killiny et al , 2017; Miles et al , 2017; Ramadugu et al , 2016; Richardson and Hall, 2013). Traditional breeding through crossing elite cultivars with resistant materials can achieve this objective.…”
Section: Introductionmentioning
confidence: 99%
“…There are no known resistant citrus varieties or scion-rootstock combinations, although some are more susceptible than others (Fan et al, 2013;Folimonova et al, 2009). Some tested citrus relatives are resistant to HLB, but it remains unclear whether this is a result of plant processes or non-colonization by HLB vectors (Ramadugu et al, 2016).…”
Section: Walled Phloem-limited Bacteriamentioning
confidence: 99%
“…Regarding the search for alternatives using plant resistance, Ramadugu et al [119] found resistant accessions of Australian desert lime (Eremocitrus glauca), curry leaf (Bergera koenigii), Japanese prickly ash (Zanthoxylum ailanthoides), Hesperethusa (Naringi crenulata), orange jasmine (Murraya paniculata), and white sapote (Casimiroa edulis), in which the pathogen replicated transiently, but could not establish in the plant. The authors suggested that accessions of Eremocitrus and Microcitrus (ranked as tolerant), which are sexually compatible with Citrus, have the potential for the generation of HLB resistant cultivars.…”
Section: Plant Genetic Resistancementioning
confidence: 99%